Kompetensi Tutor Satuan Pendidikan Nonformal dalam Penerapan Model Pembelajaran Reflektif - Rosmilawati, Ila; Meilya, Ika Rizqi; Darmawan, Dadan (Journal of Nonformal Education and Community Empowerment, 2020)
This study aims to explore the ability of non-formal education tutors in implementing a reflective learning model. The quality teaching in non-formal education environment will be largely determined by the competence of tutor, one of which is mastery of reflective learning methods. Reflective action as an alternative teaching method is an important part for tutors to increase their professionalism. A total of twenty-five tutors were involved in the workshop on the application of reflective learning model, and then it was observed to what extent the tutor’s ability to plan, implement, and evaluate reflective activities in learning. Tutors were also interviewed to measure their understanding of reflective pedagogy. The data was collected from the informan were then analyzed using thematic analysis. The results showed that the tutors from PKBM Insan Madani and PKBM Abdi Pertiwi in Serang City, Banten, practiced reflective action in simple way, but did not understand the basic concepts of the reflective learning model. Tutors also understand the benefits of reflective action in classroom learning, both the benefits for the tutors themselves in order to increase the professionalism, as well as the benefits for students, namely to asses self-satisfaction in the learning process and outcomes.